2017
DOI: 10.1038/srep42582
|View full text |Cite
|
Sign up to set email alerts
|

Microglia preconditioned by oxygen-glucose deprivation promote functional recovery in ischemic rats

Abstract: Cell-therapies that invoke pleiotropic mechanisms may facilitate functional recovery in stroke patients. We hypothesized that a cell therapy using microglia preconditioned by optimal oxygen-glucose deprivation (OGD) is a therapeutic strategy for ischemic stroke because optimal ischemia induces anti-inflammatory M2 microglia. We first delineated changes in angiogenesis and axonal outgrowth in the ischemic cortex using rats. We found that slight angiogenesis without axonal outgrowth were activated at the border … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 61 publications
6
111
1
1
Order By: Relevance
“…Interestingly, metabolic stress by OGD or aglycemia alone did not affect primary microglia function or their expression of inflammatory markers. In the literature, pro-inflammatory effects of OGD on primary microglia in culture have been described [14,15], albeit sometimes in a shallow range [16] and with a heterogeneous response of different pro-inflammatory markers [17]. In line with our results, another study also did not observe significant changes in inflammatory markers in primary microglia after OGD [18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, metabolic stress by OGD or aglycemia alone did not affect primary microglia function or their expression of inflammatory markers. In the literature, pro-inflammatory effects of OGD on primary microglia in culture have been described [14,15], albeit sometimes in a shallow range [16] and with a heterogeneous response of different pro-inflammatory markers [17]. In line with our results, another study also did not observe significant changes in inflammatory markers in primary microglia after OGD [18].…”
Section: Discussionsupporting
confidence: 91%
“…In line with our results, another study also did not observe significant changes in inflammatory markers in primary microglia after OGD [18]. Taken together, literature data on microglia OGD is contradictory, which may be attributed to the heterogeneity of primary microglia and methodical differences in the OGD setting [14][15][16][17][18] as well as species differences [19]. Studies on aglycemia in microglia are scarce, and thus far only two studies focused on this topic, finding an increased proinflammatory response of microglia after aglycemia [20,21].…”
Section: Discussionsupporting
confidence: 90%
“…Mac-1 is a β2 integrin that is constitutively expressed on the surface of microglia. Mac-1 upregulation after oxygen-glucose deprivation (OGD) preconditioning has been found to enable microglia to cross the BBB and reach the rat brain parenchyma [69]. In addition, a study in C57BL/6 mice revealed that M2-like macrophages were able to infiltrate the ischaemic hemisphere via the choroid plexus-cerebrospinal fluid (CSF) route, thus suggesting that autologous transplantation of M2-like microglia into the CSF might be a promising treatment strategy for ischaemic stroke [158].…”
Section: Cellular Therapies For Stroke That Target Microgliamentioning
confidence: 99%
“…Ekdahl et al [162] found that microglia pre-conditioned to a protective phenotype could support neurogenesis, progenitor proliferation and survival, migration and differentiation of newly formed neurons in the adult brain following stroke. Kanazawa et al [69] found that intrathecal administration of primary microglia preconditioned in OGD conditions promoted the secretion of remodelling factors into the brain parenchyma, e.g., vascular endothelial growth factor (VEGF), TGF-β and MMP-9, thus facilitating axonal outgrowth and angiogenesis in the ischaemic cortex of rats. Administration of M1-polarised microglia has exacerbated OGD-induced neuronal death, manifested by reduced microtubule-associated protein-2 (MAP2) expression and increased lactate dehydrogenase (LDH) release, compared to microglia expressing differing inflammatory profiles.…”
Section: Cellular Therapies For Stroke That Target Microgliamentioning
confidence: 99%
“…In macrophages, the two different subsets-M1 and M2-express different MMPs [95]. MMP-9-which depicts pro-inflammatory roles in BBB opening and cytokine activation-is secreted by M2 microglia and involved as a remodeling factor during repair [96,97]. Kohkha et al further suggest that MMPs-apart from being differentially expressed in M1 and M2 subsets-might also contribute to phenotype polarization by regulating cytokine and growth factor availability [15].…”
Section: Mmps and Microgliamentioning
confidence: 99%